NON-DIPPING PHENOMENON MEASURED BY 24H-AMBULATORY BLOOD PRESSURE MONITORING IS A STRONG PREDICTOR OF LEFT VENTRICULAR HYPERTROPHY IN CHRONIC KIDNEY DISEASE. (June 2018) - Jaques, D.; Muller, H.; Martinez, C.; De Seigneux, S.; Martin, P.; Saudan, P.; Ponte, B.
Abstract : Objective: Few studies have assessed the role of 24 h ambulatory blood pressure monitoring (ABPM) in adults suffering from non-dialysis chronic kidney disease (CKD). We examined potential determinants of left ventricular hypertrophy (LVH) and mass index (LVMI) in this population. Design and method: We conducted a cross-sectional study on 69 stage 3b-5 CKD adults who had ABPM and transthoracic echocardiography performed simultaneously. Hypertension (HT) was defined as 24 h blood pressure (BP) > or = 130/80 mmHg. ABPM parameters considered were BP dipping status, BP load and BP nighttime/daytime ratio. We conducted stepwise backward multivariate linear and logistic regression to assess determinants of LVH and LVMI. ABPM parameters were considered main predictors whereas HT, ACEI/ARAII use, GFR < 30 ml/min/1.72m2, diabetes, smoking, age, gender, Hb and PTH levels were considered covariates. Results: LVH was present in 22 (31.8%) patients. In linear regression analysis, systolic (β=−13.8, 95% CI = −26.3; −1.3, p = 0.031) and mean (β=−13.5, 95% CI = −25.7; −1.2, p = 0.031) dipping statuses were negatively associated with LVMI. BP load and nighttime/daytime ABPM ratio were not associated with LVMI. In logistic regression analysis, systolic dipping status (OR = 0.27, 95% CI = 0.08; 0.91, p = 0.036) was negatively associated with LVH. Amongst covariates, eGFR < 30 ml/min/1.72m2 and HT were positively associated with LVH and LVMI. At one-year follow-up, mean dipping status on the initial ABPM remained significantly associated with LVMI (β=−19.8, 95% CI = −36.6; −3.0, p = 0.022). Conclusions: These data confirm the high incidence of LVH amongst non-RRT CKD patients and suggest that non-dipping phenomenon on ABPM is an independent and strong predictor of LVH and LVMI in this population.